Impact of 'HIV-related stigma-reduction workshops' on knowledge and attitude of healthcare providers and students in Central India: a pre-test and post-test intervention study. Issue 4 (12th April 2020) - Machowska, Anna; Bamboria, Babu Lal; Bercan, Courtney; Sharma, Megha
Abstract : Introduction: People living with HIV and AIDS (PLWHA) experience stigma and discrimination throughout their life. The consequences of stigma and discrimination are severe when enacted by healthcare providers (HCPs), and result in a delay in or poor adherence to treatment. Studies have demonstrated the presence of stigmatising behaviours among HCPs, yet only a few have presented the impact of interventions on the knowledge and attitude of practising (clinicians and nurses) and future (students) HCPs. Objectives: To evaluate knowledge, attitudes and infection risk perceptions related to HIV/AIDS among practising and future HCPs in central India. In addition, the impact of the 'HIV-related stigma-reduction workshop' using a pre-intervention and post-intervention study design was evaluated. Settings and participants: The study was conducted in 2016 at two tertiary-care hospitals and three healthcare colleges in central India. Overall, 650 HCPs (75 clinicians and 211 nurses) and students (205 medical, 123 nursing and 36 Diploma in Medical and Laboratory Technology (DMLT)) voluntarily participated in the study. Intervention: The educational intervention comprised of training in epidemiology, the transmission and treatment of the HIV infection, the rights of PLWHA, the duties of HCPs and the use of standard precautions. Results: At pre-intervention, DMLT students had the lowest and clinicians the highest knowledge scores (24% and 45%, respectively). The stigmatised attitude was reflected in all groups, the lowest among clinicians (21%) and the highest among DMLT students (34%). Improvement in the post-intervention knowledge scores was the highest in medical students (36%) and the lowest among clinicians (16%). The participants' attitudes improved between 3% and 17% across all groups. Conclusions: Significant post-intervention improvements were seen in both knowledge and attitudes in all groups. Students had a higher tendency to improve than HCPs. Further long-term studies are needed to evaluate the sustainability of the improvements in knowledge and attitudes of the participants.